2007
DOI: 10.1016/j.bbamem.2007.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Roughness of the plasma membrane as an independent morphological parameter to study RBCs: A quantitative atomic force microscopy investigation

Abstract: A novel approach to the study of RBCs based on the collection of three-dimensional high-resolution AFM images and on the measure of the surface roughness of their plasma membrane is presented. The dependence of the roughness from several parameters of the imaging was investigated and a general rule for a trustful analysis and comparison has been suggested. The roughness of RBCs is a morphology-related parameter which has been shown to be characteristic of the single cells composing a sample, but independent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(127 citation statements)
references
References 29 publications
3
122
0
2
Order By: Relevance
“…where, N is the total number of data points, z i is the height of the ith point, and z m is the mean height (19). Roughness values were measured over the entire bacterial cell surface on areas with a fixed size of 125 ϫ 125 nm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…where, N is the total number of data points, z i is the height of the ith point, and z m is the mean height (19). Roughness values were measured over the entire bacterial cell surface on areas with a fixed size of 125 ϫ 125 nm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, previous studies demonstrated roughness values, average roughness (Ra) and root-mean-square roughness (Rq), to be markers of the degree of change to cell membranes. [44][45][46] As shown in Figure 4B and C, both the Ra and Rq of two different areas increased in a dose-and time-dependent manner. The Ra and Rq values of the cells in the control group were low, indicating a smooth surface ( Figure 4A).…”
mentioning
confidence: 76%
“…This challenge is seen both at the cellular and humoral levels involving white blood cells and their significant roles in the wound healing of diabetic rats administered sildenafil citrate (Tas et al, 2011). This study which involves analysis of red blood cells count in diabetic rats with wound formation following treatment with sildenafil citrate is of significance because wound healing also depend on oxygenation which is supplied to the bodily parts via hemoglobin in the circulating red blood cells (Girasole et al, 2007;Hamed et al, 2010). The roles of nitric oxide in the regulation of vasodilation (Furchgott, 1996), control of the cell cycling and apoptosis, cell proliferation and differentiation (Weller et al, 1998) have been described in previous studies.…”
Section: Introductionmentioning
confidence: 95%